2019
DOI: 10.3390/coatings9070444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Temperature Calcined Wheat Straw Powder after Lignin Removal on Properties of Waterborne Wood Coatings

Abstract: The effect of adding wheat straw powder after lignin removal (WSPALR) and high-temperature calcined WSPALR on the hardness, adhesion, and resistance to impact, color difference, and mold resistance of waterborne coatings was studied. The results showed that the hardness was the highest of 6H when the concentration of WSPALR was 1.0%–2.0%. WSPALR and high-temperature calcined WSPALR had little effect on the adhesion and impact resistance of waterborne coatings, and the resistance to impact was about 10.0 kg cm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Adding thermochromic ink to waterborne wood coatings can change the color of waterborne coatings with the change of temperature, make the product display different colors with the change of season, and make the product more humanized and changeable. The waterborne wood coating is environmentally friendly because it does not increase VOC emissions [15,16], and it is superior to oil-based paint in environmental sustainability and performance stability [17,18]. Microencapsulation is needed to keep the entire thermochromic system together and protect it from the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…Adding thermochromic ink to waterborne wood coatings can change the color of waterborne coatings with the change of temperature, make the product display different colors with the change of season, and make the product more humanized and changeable. The waterborne wood coating is environmentally friendly because it does not increase VOC emissions [15,16], and it is superior to oil-based paint in environmental sustainability and performance stability [17,18]. Microencapsulation is needed to keep the entire thermochromic system together and protect it from the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…The band at 1732 cm −1 is the C=O group with strong and sharp characteristics, which may be aldehyde or ketone. It can be seen from Figure 4 that there were absorption peaks representing C=C-H near 810 cm −1 , and the C-O stretching vibration band and the C-C skeleton stretching vibration absorption at 1150 cm −1 [24]. When the pigment powder was added to the primer, all peaks were not disappeared apart from -OH group, which basically did not affect the discoloration effect of the pigment powder, and still had the discoloration ability.…”
Section: The Fourier Transform Infrared Spectroscopy (Ftir) Analysis mentioning
confidence: 96%
“…Huang et al [49,50] found that the reduced elastic modulus of bamboo fiber cell walls in the transverse direction was 5.91 GPa, and in the longitudinal direction, was 17.6 GPa, and the hardness was 0.37 GPa. The samples were embedded in epoxy resin, which might result in undesirable chemical modifications caused by epoxy impregnation [50,51]. Therefore, the influence of epoxy resin, the interface between the fiber and resin, and the microfibril angle of the fiber on the nanomechanical properties of PCF will be evaluated in future work.…”
Section: In Situ Nanoindentationmentioning
confidence: 99%